Research and prospects of environmental DNA (eDNA) for detection of invasive aquatic species in East Asia - Wang, Linjing; Wan, Fanghao; Qian, Wanqiang (Frontiers in Marine Science, 2023)
The issue of biological invasions in aquatic ecosystems is becoming increasingly severe in the contemporary world. Due to the lack of monitoring and management systems for aquatic invasive species, the difficulty in identifying aquatic invasive species, and the limited effectiveness of conventional control methods in aquatic environments, biological control in water bodies is comparatively more challenging than other types of interventions. In recent years, environmental DNA (eDNA) survey methods have rapidly developed in various fields, such as biological monitoring, community ecology, paleoenvironmental research, conservation biology, and invasion ecology, due to their unique advantages of being rapid, sensitive, efficient, and non-invasive. Because of these characteristics, this innovative molecular approach has gained wider acceptance and is being increasingly utilized for the detection of biological diversity in aquatic environments. Furthermore, it has emerged as a novel technology to address the pressing and significant issue of aquatic invasive species in the vast freshwater and marine resources of the East Asian region. This paper summarizes a variety of literature sources to summarize the major aquatic invasive species in East Asian countries and the current application status of eDNA technology in their survey processes. Using China as a case study, it expounds on the prospective incorporation of the 4E strategy with eDNA technology for the surveillance of biological invasions. Furthermore, it explores the potential prospects of eDNA technology in species diversity management and policy formulation, offering theoretical guidance for establishing aquatic invasive species monitoring systems. From a technological standpoint, the integration of eDNA technology with the 4E strategy holds significant potential for application, thereby offering a promising reference for the formulation of policies related to the management of aquatic biological invasions and biodiversity.